Rancang Bangun Mesin CNC 2 Sumbu - Firman Ridwan; Arif Novriheldi (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
Nowadays, high accuracy and precision of products have become a major requirement by the manufacturer. It can only be achieved by using a controlled machine such as CNC machine. On the other hand, most of home industries have conventional production machines and manually operated. Unavailable precisian machines cause difficulties to achieve such products. In most cases, capability of home industries to buy high cost machines is limited. Therefore, it is then to be the backdrop of designing a simple construction and its control system for a low cost CNC plasma cutting machine. A low cost CNC plasma cutting machine was designed and expected to be realible in controlling the movement of the axis preciselly during cutting process. The result of this study showed that the machine was capable of achieving the following levels of precision up to 0.05 mm for the X-axis with a deviation of 0.04 mm. Meanwhile the Y axis was obtained up to 0.08 mm with a deviation of 0.057. The results indicate that the achieved accuracy is higher compared to the manual cutting.